GUT MICROBIOTA AS A KEY MODULATOR OF METABOLIC SYNDROME AND OBESITY: MECHANISMS, CLINICAL EVIDENCE, AND THERAPEUTIC PERSPECTIVES - Wymoczył, Karolina; Cieślak, Natalia; Chodkowska, Agata; Cyrkler, Aleksandra; Czyżak, Kamila; Marzec, Urszula; Dąbek, Karol; Rajca, Eliza; Giza, Agnieszka; Giza, Paulina (International Journal of Innovative Technologies in Social Science, 2026)
The global escalation of obesity and metabolic syndrome (MetS) represents a significant challenge to public health systems (World Health Organization, 2024). Emerging evidence identifies the gut microbiota—the complex community of microorganisms inhabiting the gastrointestinal tract—as a critical environmental factor influencing host energy homeostasis and inflammation (Evans et al., 2013). This review examines the intricate mechanisms through which gut dysbiosis contributes to the pathogenesis of obesity and MetS, including altered energy extraction, modulation of lipid metabolism, and the induction of chronic low-grade inflammation via metabolic endotoxemia (Cani et al., 2007). We synthesize current clinical evidence from human cohort studies that correlate specific microbial signatures with metabolic health (Le Chatelier et al., 2013). Furthermore, this article explores therapeutic perspectives, evaluating the efficacy of probiotics, prebiotics, and fecal microbiota transplantation (FMT) in restoring metabolic balance (Vrieze et al., 2012). A core focus is placed on the integration of advanced bioinformatic frameworks, such as the QIIME 2 pipeline and Random Forest machine learning architectures, which facilitate the transition from taxonomic description to functional, predictive modeling of the gut-metabolic axis (Knight et al., 2018; Zeevi et al., 2015). By integrating findings from molecular biology, systems engineering, and clinical trials, we conclude that the gut microbiota is a viable target for personalized therapeutic interventions in metabolic diseases (Fan & Pedersen, 2021).